Does Prior Nasal Airway Surgery Impact Hypoglossal Nerve Stimulation for Obstructive Sleep Apnea? - Vaibhav H. Ramprasad; Anna Matzke; Lauren Makey; Eugene Chio; Armin Steffen; Joachim T. Maurer; Clemens Heiser; Ryan J. Soose (OTO Open)
Abstract Objective Nasal surgery can improve patient‐reported obstructive sleep apnea (OSA) outcomes as well as adherence with medical device treatments. The aim of this study was to examine whether previous nasal surgery was associated with hypoglossal nerve stimulation (HNS) therapy outcomes. Study Design Retrospective observational cohort study was performed utilizing the multicenter international HNS registry (ADHERE). Methods Propensity score matching generated a cohort of HNS patients with prior nasal surgery (NS) and a comparable cohort without prior nasal surgery (WNS). Data included demographics and therapy outcome measures including apnea‐hypopnea index (AHI), Epworth Sleepiness Scale (ESS), therapy use, and responder rate. Student's t‐test was used to compare normally‐distributed numeric data, Fisher's exact test to compare categorical data, and 1‐sided t‐tests to determine noninferiority. Results From the ADHERE dataset, 169 HNS patients were identified and matched from each cohort. AHI reduction was 21.01 ± 17.94 in the WNS cohort and 18.39 ± 16.4 in the NS cohort (P = .162). ESS reduction in the WNS cohort was 4.85 ± 4.98 and 4.48 ± 5.83 in the NS cohort (P = .528). Therapy use was similar, 5.67 ± 1.95 in WNS and 5.97 ± 2.06 in NS (P = .181). Responder rate was also similar in WNS (64.5%) and NS (62.1%) groups (P = .735). Conclusion Prior nasal surgery was not a predictor of HNS therapy response or adherence. Future prospective studies of HNS candidates with nasal airway obstruction may better determine the role of adjunctive nasal surgery in this population.